2010
DOI: 10.1111/j.1542-4758.2009.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus bovis bacteremia related to colon adenoma in a chronic hemodialysis patient

Abstract: We report the case of a 54-year-old hemodialysis patient who presented with recurrent fever due to Streptococcus bovis bacteremia related to colonic tubulovillous adenoma. Following polypectomy and broad-spectrum antibiotic therapy, the patient totally recovered. In this paper, we discussed the relation between S. bovis bacteremia, colonic adenomas, and hemodialysis. Awareness of this association is critical for early diagnosis and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The relationship between S. bovis/gallolyticus infection and the progressive development of malignant disease in preneoplastic adenomatous polyps was supported by recent reports [39,73,74]. Interestingly, S. bovis/gallolyticus was found to be mildly associated with some benign lesions (diverticulosis, inflammatory bowel disease, cecal volvulus, perirectal abscess hemorrhoids, and benign polyps), while it was strongly associated with most malignant diseases (cancer and neoplastic polyps) of the colon [2,39,67,70,75,76].…”
Section: The Association Of S Bovis/gallolyticus With Colorectal Adementioning
confidence: 57%
“…The relationship between S. bovis/gallolyticus infection and the progressive development of malignant disease in preneoplastic adenomatous polyps was supported by recent reports [39,73,74]. Interestingly, S. bovis/gallolyticus was found to be mildly associated with some benign lesions (diverticulosis, inflammatory bowel disease, cecal volvulus, perirectal abscess hemorrhoids, and benign polyps), while it was strongly associated with most malignant diseases (cancer and neoplastic polyps) of the colon [2,39,67,70,75,76].…”
Section: The Association Of S Bovis/gallolyticus With Colorectal Adementioning
confidence: 57%
“…The remaining causes of CRB are a various Gram‐negative bacilli (approximately 30%), and 10% due to mixed infections and fungi 9 . The incidence of CRB in hemodialysis patients due to Gram‐negative bacilli and other unusual microorganisms, such as Serratia spp ., Acinetobacter spp ., Citrobacter spp ., and Agrobacterium radiobacter is increasing 10 . Generally, C. testosteroni infections have a favorable outcome, and the majority of the infected patients recovered after antibiotic therapy and removal of the vascular access device.…”
Section: Discussionmentioning
confidence: 99%
“…9 The incidence of CRB in hemodialysis patients due to Gram-negative bacilli and other unusual microorganisms, such as Serratia spp., Acinetobacter spp., Citrobacter spp., and Agrobacterium radiobacter is increasing. 10 Generally, C. testosteroni infections have a favorable outcome, and the majority of the infected patients recovered after antibiotic therapy and removal of the vascular access device. For example, Le Moel et al reported a case of C. testosterone bacteremia in a 75-year-old woman with breast cancer whose origin was from a central venous catheter (CVC).…”
Section: Discussionmentioning
confidence: 99%
“…Several Streptococcus species represent serious invasive pathogens, often associated with wound infections, sepsis, abscesses and dental caries in immunocompromised or cancer patients (Moet et al , 2007; Fernández-Ruiz et al , 2010; Al-Jashamy et al , 2010). The association of S. bovis with endocarditis (Gupta et al , 2010), colon cancer (Boleij et al , 2009) and colon adenoma (Kahveci et al , 2010) has also recently been reported. This species is therefore considered a potential pathogen.…”
Section: Introductionmentioning
confidence: 93%